Stone Money of Yap as an Early form of Money in the Economic Sense - Paul F. Gentle (Financial Markets, Institutions and Risks)
This article examines the special case of stone money, in Yap as a store of value, medium of exchange and unit of account, which are the three traits required for something to be considered money, in the economic sense. When confidence in a system of currency with coins is present, this more conventional form of money takes precedence. A respected economic form of currency with coins has all three elements of money: medium of exchange, store of value and unit of account. Though clearly, in a certain time period, stone money was the principle type of money. To a lesser extent, beads and shell were used as money. So, for a period of time, stone money, along with some use of beads and shells, constituted the medium of exchange. The focus of this article is on the stone money of Yap. Stone was obtained by quarrying on the island of Palau, some 500 to 600 years ago. A very interesting type of money in the past, was the stone money of Yap, more formally known as Rai, or Fei. These were doughnut-shaped, carved disks of normally calcite and, up to 4 meters (12 feet) in diameter. However, there are more smaller ones, with the smallest being as little as 3.5 centimeters (1.4 inches) in diameter. The people of Yap attributed value to the Rai. After the use of Rai faded away, German Marks and then later Japanese Yen and finally the U.S. Dollar, were the monetary standard. The prior use of Rai is the main interest of this article. Today Yap is an independent country, in a “free association” with the United States. A curriculum that somewhat resembles an American one is taught in schools on Yap. Tourism to Yap is an important activity. Currently, the U.S. dollar serves as the basis for money in the nation of Yap. It has been found that this stone money met the three criteria necessary for them to be an early type of money.